1994
DOI: 10.1093/nar/22.19.3895
|View full text |Cite
|
Sign up to set email alerts
|

Negative electrospray ionization mass spectrometry of synthetic and chemically modified oligonucleotides

Abstract: We report here on the analysis of synthetic oligonucleotides by electrospray ionization mass spectrometry (ESI-MS). After intensive removal of salt ions (especially sodium cations), negative ion mass spectra, allowing mass measurement with an accuracy of 0.01%, were obtained on several oligonucleotides up to 80 nucleotides. In most cases, the resolution was sufficient to observe n-1 and n-2 forms due to internal deletions during automated synthesis, and to identify the missing nucleotides. A 132-mer, whose siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 17 publications
5
132
0
1
Order By: Relevance
“…In the past, several strategies were developed to obtain sufficiently pure DNA samples. Most involved either ethanol precipitation (16,21,22,33,(38)(39)(40)(41) or centrifugation through appropriate filter systems/spin columns (30)(31)(32)34,41) followed by microdialysis (42)(43)(44) or incubation with cation exchange particles (17) for final desalting.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several strategies were developed to obtain sufficiently pure DNA samples. Most involved either ethanol precipitation (16,21,22,33,(38)(39)(40)(41) or centrifugation through appropriate filter systems/spin columns (30)(31)(32)34,41) followed by microdialysis (42)(43)(44) or incubation with cation exchange particles (17) for final desalting.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade the development of electrospray ionisation mass spectrometry (ESI-MS) has allowed accurate mass measurements to be performed on relatively large oligonucleotides including plasmid DNA. [15][16][17][18][19] ESI-MS has also been used for the characterisation of covalent [20][21][22][23][24] and non-covalent [25][26][27][28] drug-DNA complexes. For example, ESI-MS studies on DNA bound to the antibiotic hedamycin revealed that the drug selectively binds to specific DNA sequences and significantly increased the stability of duplex DNA in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-crosslinked peptide conjugates containing RNA mono-and dinucleotides were not detected in the tryptic peptide mixtures. The low ionization efficiency of nucleic acids by electrospray in positive ion mode often causes signal suppression of crosslinked peptide-RNA entities (Potier et al 1994;Sannes-Lowery et al 1997). Also, unknown photoreaction mechanism of nucleotides, adverse reactions caused by long UV irradiation (Kubasek et al 1993), hampers prediction of the final products.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%